"Academic racism" and the neglected scholarship of the anatomist M. Wharton Young, MD, PhD (1904–1986). (February 2018) - Heywood, Peter
Moses Wharton Young, MD, PhD (1904–1986), was an African American Professor of Neuroanatomy at Howard University College of Medicine from 1934 to 1973, during which time he authored about 100 publications on topics that included baldness, asthma, glaucoma, and, most importantly, the structure and function of the inner ear and the pathophysiology of blast injuries. Much of Young's research was ignored during his lifetime, raising the question whether this professional neglect was an instance of "academic racism."